Cerdas dan Bijak Menggunakan Internet Sehat Bagi Guru Di Madrasah Aliyah Negeri 11 Jakarta - Firdaus, Indra Cahya; Wijoyo, Agung; Prasetiyo, Sofyan Mufti (Universitas Pamulang, 2025)
This community service activity aimed to enhance digital literacy and ethical awareness in digital media among teachers at Madrasah Aliyah Negeri 11 Jakarta. Using a participatory educational approach, the program was delivered through seminars and interactive training sessions focusing on key issues such as digital ethics, cybersecurity, and healthy internet usage in educational practices. Evaluation results indicated a significant improvement in teachers' understanding of responsible and intelligent internet use. Participants also demonstrateda strong commitment to applying digital citizenship values within the school environment. This initiative not only strengthened teachers’ capacity as digital literacy agents but also led to the formation of a collaborative digital community among educators. The intervention serves as a critical foundation for cultivating a healthy and productive digital culture in the education sector. Keywords: digital literacy, healthy internet, digital ethics, madrasah teachers, digital culture.